Responses of tea clones to drought in Southern Tanzania - Burgess, Paul J. (Cranfield University, 1992)
A line-source experiment, planted in August 1988, was used to quantify the yield responses of six tea (Camellia sinensis) clones to drought in Southern Tanzania. The selected clones (1, 6/8, SFS150, S15/10, 207 and K35) are scientifically and/or commercially important in eastern Africa. Drought treatments were imposed during the latter part of 1989 and 1990. Soil water deficits were estimated using a water balance model, validated using a neutron probe. The maximum yield of made tea, from June 1990 to May 1991, was 3760 kg ha⁻¹ for clone S15/10, compared to 2210-2640 kg ha⁻¹ for the other clones. Drought resistances, assessed from the relative yield reduction below the maximum, were greatest for clones 1 and SFS150. The clonal attributes determining these responses were examined in terms of dry matter production and partitioning,components of yield, and plant water status, and were used to determine selection criteria for high yielding and/or drought resistant clones. The high yield of clone S15/10 resulted from greater partitioning of dry matter to leaf and harvested shoots (51%) than the other five clones (34-39%). The conversion efficiency for four of the fully irrigated clones was 0.33-0.55 g MJ-⁻¹ intercepted total solar radiation. Drought resistance was related with leaf measurements of photosynthetic rate per unit stomatal conductance (A/g). In a comparison of droughted plants, resistance was related to reduced incidence of Phomopsis theae, reduced leaf abscision and high xylem water potentials. Measurements of stomatalconductance highlighted calibration problems with transient and steady state porometers. Clone SFS150 had the lowest base temperature for shoot extension (8.9°C) and therefore a more even seasonal distribution of yield than the other clones. Base temperatures for shoot development were 1.7-3.5°C lower than those for extension. The dry matter content of harvested shoots typically ranged from 24.2% for clone 1 to 20.7% for clone SFS150. Partitioning of dry matter to leaves and green stem for high yield, a high A/g ratio for drought resistance, and low base temperatures for improved yield distribution are proposed as selection criteria.